2005
DOI: 10.1111/j.1432-2277.2005.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of cadaveric renal allografts contaminated before transplantation

Abstract: Summary This analysis was performed to define the incidence of pretransplant microbial contamination of donor kidneys, and to assess the resultant morbidity including infections requiring therapy, and graft loss. Case records of all 638 renal allograft recipients patients transplanted in our centre during the period June 1990 to October 2000 were studied. All the recipients were given a single dose of intravenous antibiotics at the time of induction of anaesthesia. A total of 775 microbiology reports on perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
4
17
1
Order By: Relevance
“…The overall contamination rate was 7.2%, similar to the 4.2–28% reported in previous studies 15. Several publications report yeasts in PF, 1.7–2.75%; our rate was lower at 0.8% 16 17.…”
Section: Discussionsupporting
confidence: 88%
“…The overall contamination rate was 7.2%, similar to the 4.2–28% reported in previous studies 15. Several publications report yeasts in PF, 1.7–2.75%; our rate was lower at 0.8% 16 17.…”
Section: Discussionsupporting
confidence: 88%
“…Differences between published contamination rates may be explained by inconsistent use of iodine duodenum decontamination, proton‐pump inhibitors in the intensive care unit, and other variations in the retrieval and microorganism identification protocols. As a point of comparison, the rates of microbial contamination of the preservation medium for other organs are as follow: 9–57% for kidneys , in 27% to 62% for livers , in 45–64% for heart valves , in 29% for lungs , and in 14–29% for cornea . In the present study, we identified a majority of Gram‐positive bacteria namely Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, a strict quality control process must be implemented. The existing literature describes variable rates of solid organ (kidney, liver, heart, lung, and cornea) transport media microbial contamination, ranging from 9% to 64% (median 41%) [6][7][8][9][10][11]. In comparison, pancreas preservation medium contamination rates were reported between 28% and 62% (median 31%) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensual definition of bacterial PS contamination in kidney transplantation. Previous studies have reported PS contamination in between 2.2% and 38.7% of tested samples . This variation could be explained by the lack of a proper definition and the use of various culture methods.…”
Section: Discussionmentioning
confidence: 90%
“…PS contamination is a common cause of early post‐transplant infection, with a reported incidence of 2.2–38.7%, and may be a major cause of early morbidity after transplantation. However, prophylactic antibiotic therapy seems to prevent early post‐transplant infection .…”
Section: Introductionmentioning
confidence: 99%